Finding the "both/and": Balancing informal and formal music learning. (August 2020) - Hess, Juliet
This article explores the informal and formal learning experiences of 20 activist-musicians. Multiple activist-musicians utilized the informal learning strategies Green identifies. More than half of the participants, however, bemoaned the lack of more formal music education. They noted that they valued informal musical learning practices and also wished that they had experienced more of a balance between formal and informal music learning strategies in their music education. Many of the participants identified as being self-taught. In interviews, they shared ideas about teaching themselves and "figuring things out" musically. They discussed both wanting to move away from theory and needing theory. They further preferred a structured approach to education before moving to a more "free" pedagogy. Ultimately, they noted that the human relationships intrinsic to musicking may transcend the need for "training." This article concludes by exploring implications of implementing a balance between formal and informal learning for K-12 schooling and teacher education.